Kid athletes : true tales of childhood from sports legends - Stabler, David; Horner, Doogie (Philadelphia, PA : Quirk Productions, Inc., 2015)
A collection of anecdotes from the childhoods of famous athletes, including Babe Ruth, Danica Patrick, Peyton Manning, and others.
Includes bibliographical references (p. 198-202) and index.
Booklist starred
Horn Book
Booklist starred, September 2015
Horn Book, April 2016
6.2
Keywords: Athletes -- Juvenile literature; Athletes; Athletes